Condições de vida, produção e saúde em uma comunidade de mineiros e artesãos em pedra-sabão em Ouro Preto, Minas Gerais: uma abordagem a partir da ocorrência de pneumoconioses - Olivia Maria de Paula Alves Bezerra (2002)
This study had the purpose of knowing life, production and health conditions of soapstone miners and handcraft workers, in a rural area in Ouro Preto, Minas Gerais, Brazil, called Mata dos Palmitos. A traverse descriptive epidemiologic study was accomplished. It was assampled, based in primary and secondary data an of interdisciplinar and interinstitutional nature. The analysis included soapstone history in municipality and in the place, natural environment, social environment and damages for health related to soapstone dust, especially pneumoconiosis (talcosis) ocurrence in the workers. The results suggested precarious life, production and health conditions, caracterized, among other aspects, by ocurrence of five cases (4,3%) of well-defined talcosis and eleven cases (9,4%) of incipient talcosis. Because the analysis of dust revealed presence of asbestos breathable fibers of the amphibole group (tremolite-actinolite), the possibility of talcoasbestosis was suggested. The data suggest the necessity of changes in the work process. Besides, health surveillance of the exposed workers should be developed, as well as the actions to turn better general life conditions of the population.